Faktor-faktor yang Mempengaruhi Kepatuhan Pengobatan Tuberkulosis: A Systematic Review - Vivi Meiti Berhimpong; Tintin Sukartini (FORIKES, 2021)
Background: The biggest problem of transmission of infectious diseases to date was disobedience in undergoing treatment which makes patients resistant to drugs and threatens other public health by increasing morbidity and mortality (mortality). Objective: To identify factors that influence the leveled of patient compliance with tuberculosis treatment. Methods: This systematic review was based on preferred reporting items for systematic reviews and meta-analyses (PRISMA). The database used in this studied was Scopus, ProQuest and PubMed were limited to the last 5 years of publication from 2016 to 2020, full-text article and in English. The keywords used were